The combined influence of classification and mechanical activation of kaolin on the structure and properties of geopolymer - Roland Szabó; Ferenc Kristály; Fanni Dolgos; Mária Ambrus; Gábor Mucsi (Case Studies in Construction Materials)
The use of raw kaolin is limited in the production of geopolymers due to its low reactivity. However, thermal and/or mechanical activation processes can primarily increase its reactivity. This study focused on the preparation of kaolin by classification and mechanical activation to produce geopolymer and the quantification of the phase changes that occur during mechanical activation and geopolymerisation. The raw kaolin was classified as suspensions with different volume concentrations (1, 2, 4, and 6 V/V%) in a hydrocyclone, and the kaolinite-rich product of the classification with 4 V/V%, was mechanically activated in a high-energy stirred media mill for 1, 3, 5, 10, and 20 minutes. The milled samples were alkali-activated with 8 M sodium hydroxide solution. According to the X-ray diffraction (XRD) results of the milled kaolin samples, the prolonged milling time resulted in an overall decrease in kaolinite and an increase in amorphous content. The effect of mechanical and mechanochemical activation in the geopolymerization process was investigated using Fourier transform infrared spectroscopy (FTIR), XRD, and compressive strength measurements. A positive correlation was found between the milling time, the yield of the amorphous gel, and the compressive strength. Both the density and the uniaxial compressive strength of the geopolymer showed an exponential increase with the milling time of the classified kaolin. The initial, 1.44 MPa compressive strength of the raw kaolin geopolymer could be improved to 2.29 MPa (59 % increase) by the classification, and more than five times higher compressive strength (7.95 MPa) could be achieved by further milling for 20 mins. The XRD results proved that the combined development of nanocrystalline and amorphous products could be beneficial, acting as a reinforcing medium. This research may help contribute to a better understanding of the structural changes (phase transformations) in geopolymers using classified and mechanically activated kaolin and promote their applicability in the construction industry.